X-RAY FLOURESCENCE (XRF) ANALYSIS OF ROCK AND SOIL SAMPLES FROM A MAGNETIC INTRUSIVE ROCK IN OBA AKOKO, NIGERIA. (JOURNAL OF ADVANCES IN PHYSICS, 2016)
Nigerians had witnessed constant crash in the price of crude oil in the international market in the last couple of years to date. Therefore, Nigerians government is making concerted efforts to diversify Nigerian economy by shifting focus to other sources of mineral resources apart from petroleum. Aside from Ajaokuta iron and steel company, Oba Akoko a town in Ondo State Nigeria, has a magnetic intrusive rock which is likely one of the available mineral resources government is going to consider.